Mentoring for excellence: A constructivist approach to developing pre-service English language teachers’ skills - Al-Barakat, Ali Ahmad; Alakashee, Bushra; Kanaan, Eid; Al-Hassan , Omayya M; AlAli, Rommel M; Abdullatif, Ali K; Aboud, Yusra; Zaher, Ashraf (Research Journal in Advanced Humanities, 2026)
This study examines the pivotal role of mentor teachers in fostering constructivist learning experiences among pre-service English teachers during field-based training. Data were collected from a convenience sample of 177 pre-service teachers using a structured questionnaire, providing robust insights into the effectiveness of mentorship practices. The instrument assessed four core dimensions: lesson planning and organization, demonstration of constructivist strategies, support and guidance, and feedback and assessment practices. Findings indicated that mentor teachers play a critical role in developing learner-centered instructional skills. They provide structured lesson planning frameworks, model effective constructivist strategies, offer continuous guidance, and deliver constructive feedback, all of which enhance pre-service teachers’ instructional confidence, pedagogical reasoning, and ability to foster critical thinking, creativity, and active learner engagement. The results suggest that mentorship functions not only as a tool for knowledge transfer but also as a transformative mechanism for professional growth and reflective practice. These results underscore the essential contribution of mentorship in bridging theory and practice, highlighting the need for structured mentor training, reflective guidance sessions, and multi-method evaluation approaches. The study provides empirical evidence that systematic mentorship programs are instrumental in equipping pre-service English teachers with the competencies required to implement effective constructivist pedagogy. Future research should explore how the intensity and duration of mentorship influence the acquisition and internalization of constructivist teaching practices.